Sip N Bite cafe / Amirul Nadim Ruslan - Amirul Nadim, Ruslan (2020)
Sip N Bite cafe is determined to become a daily necessity for coffee addicts. It is also a place where we will provide a friendly, comfortable atmosphere where the customer can receive quality food and service with affordable price. We also will offer a variety of choices of coffee. What distinguishes our cafe is its diversity traditional snacks that we provided. Customers can try to escape all the stresses and meet your friends or do your work, in all one. For the convenience of our customers, we provide some laptops or you can bring your own. The kind of customer that we can sell our product or our product target are those business type person and students. They can be found typing on their laptop in an effort to complete their job and assignment. Another group would be those teenagers and socializer. Besides, the coffee lover is looking for particular tastes of coffee. If they love it, they won’t hesitate in promoting our cafe to all their circles. Sip N Bite will be operated as a Sole Proprietorship. Overall management will be the responsibility of the owner. There will be General Manager, Finance Manager and Operation Manager. Under operation will be barista, cashier, pantry worker, waiter and wash disher. For administrative or organizational expenditure will be cost around RM40,380 while marketing plan will be around RM7,150. In operation budget, including machines, equipment, raw materials and overhead expenses, we need RM12,850 excluding the sponsors to survive the business operation. Our profit will be estimated at RM475,000 in 2020. While our profitability in 2021 and 2022 is estimated to be RM489,110 and RM493,906.